Alfvénic ion temperature gradient activities in a weak magnetic shear plasma. (9th January 2017) - Chen, W.; Ma, R. R.; Li, Y. Y.; Shi, Z. B.; Du, H. R.; Jiang, M.; Yu, L. M.; Yuan, B. S.; Li, Y. G.; Yang, Z. C.; Shi, P. W.; Ding, X. T.; et al.
Abstract: We report the first experimental evidence of Alfvénic ion temperature gradient (AITG) modes in HL-2A Ohmic plasmas. A group of oscillations with and is detected by various diagnostics in high-density Ohmic regimes. They appear in the plasmas with peaked density profiles and weak magnetic shear, which indicates that corresponding instabilities are excited by pressure gradients. The time trace of the fluctuation spectrogram can be either a frequency staircase, with different modes excited at different times or multiple modes may simultaneously coexist. Theoretical analyses by the extended generalized fishbone-like dispersion relation (GFLDR-E) reveal that mode frequencies scale with ion diamagnetic drift frequency and, and they lie in KBM-AITG-BAE frequency ranges. AITG modes are most unstable when the magnetic shear is small in low pressure gradient regions. Numerical solutions of the AITG/KBM equation also shed light on why AITG modes can be unstable for weak shear and low pressure gradients. It is worth emphasizing that these instabilities may be linked to the internal transport barrier (ITB) and H-mode pedestal physics for weak magnetic shear.